Lung function, inflammation and cardiovascular mortality in Africans - Breet, Yolandi; Schutte, Aletta E.; Huisman, Hugo W.; Eloff, Fritz C.; Du Plessis, Johan L.; Kruger, Annamarie; Van Rooyen, Johannes M. (European journal of clinical investigation, 2016)
Background The link between impaired lung function and cardiovascular outcome is well established in European and American populations. It is possible that this association may be driven by a systemic spillover of inflammation occurring within the lungs. As several studies have found an increased level of inflammatory markers in African populations, we aimed to establish the contribution of lung function in predicting all‐cause and cardiovascular mortality in Africans, whilst taking inflammatory markers into account. Design We followed 1442 black South Africans from the North West Province participating in the South African leg of the Prospective Urban and Rural Epidemiology (PURE) study, over a five‐year period. Spirometry, cardiovascular and metabolic measures were performed, and cardiovascular mortality as well as all‐cause mortality used as endpoints. Results In univariate Cox regression models, both forced expiratory volume in 1‐s (FEV1) and forced vital capacity (FVC) predicted all‐cause (P = 0·022; P < 0·001) and cardiovascular mortality (P = 0·004; P < 0·001). In multivariate adjusted standardized Cox regression analyses, only FVC predicted cardiovascular mortality independent of several covariates (hazard ratio, 0·57 [0·35–0·94]), including C‐reactive protein (CRP). When CRP was replaced by interleukin‐6 in the model, the significance of FVC was lost (hazard ratio, 0·85 [0·55–1·30]). Conclusion FVC, but not FEV1, is a strong predictor of both all‐cause and CV mortality in black South Africans, which may be mediated by inflammation.